2001
DOI: 10.1074/jbc.m008295200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exon 2-encoded β-Domain of the von Hippel-Lindau Tumor Suppressor Protein

Abstract: Sporadic clear cell renal carcinomas frequently harbor inactivating mutations in exon 2 of the von Hippel-Lindau (VHL) tumor suppressor gene. Here, we examine the effect of the loss of exon 2-encoded ␤-domain function on VHL biochemical properties. Exon 2-encoded residues are required for VHL-mediated NEDD8 conjugation on cullin-2 and assembly with hypoxia-inducible factor ␣ (HIF␣) and fibronectin. These residues are not essential for VHL ability to assemble with elongin BC/cullin-2, to display E3 ubiquitin li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 46 publications
3
40
0
1
Order By: Relevance
“…Ethanol was aspirated and residual was allowed to air dry at 4jC. Cells were stained for 1 hour at room temperature with anti-fibronectin antibody as described in (29). Staining was visualized with a Ziess Axiovert S100TV microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Ethanol was aspirated and residual was allowed to air dry at 4jC. Cells were stained for 1 hour at room temperature with anti-fibronectin antibody as described in (29). Staining was visualized with a Ziess Axiovert S100TV microscope.…”
Section: Methodsmentioning
confidence: 99%
“…28 By performing coimmunoprecipitation experiments, we found that the α-domain of pVHL directly interacts with p53, and this endogenous interaction was strengthened under DNA damaging conditions. The β domain of pVHL is believed to have a role in tumor formation, but its α domain also has an important function in tumorigenesis, 29 as it is required for forming a complete ubiquitin ligase complex, which recruits Elongin C-containing proteins. Therefore, we speculated that p53-binding to the α-domain of pVHL would compete with Elongin C. Interestingly, an increase in Elongin C interrupted the p53-pVHL interaction, implying that this interaction has no influence on the ubiquitin-mediated degradation of p53.…”
Section: Coupling Of Pvhl and P53: A Novel Hif-independent Tumor Suppmentioning
confidence: 99%
“…However, the binding with HIFα occurs via the β-domain, which is missing in the pVHL 172 Bonicalzi et al 2001). Such domain is also essential for VHL interaction with the chaperonincontaining t-complex polypeptide 1 (CCT), a cytosolic molecular chaperone that assists in the folding of actin, tubulin and other cytosolic proteins.…”
Section: Introductionmentioning
confidence: 99%